Assessing knowledge, attitude, and practice of healthcare personnel regarding biomedical waste management a systematic review of available tools - Mannocci, Alice (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2020)
Biomedical waste (BMW) management is an important commitment of hospitals both in terms of the possible infectious risk and from the financial point of view. Monitoring the knowledge, attitude, and practice (KAP) of healthcare professionals on this topic represents a source of information on BMW management. The aim of this study is to perform a systematic review to identify the reliable and valid tools able to assess the KAP of professionals in healthcare centers to manage BMW. Two databases (PubMed and Scopus) were searched on 10 May 2018 for cross-sectional studies with tools on BWM management, including original research studies from peer-reviewed journals, case studies, and review studies. Information on validation and reliability were collected. Methodological quality was assessed using the Newcastle-Ottawa scale for cross-sectional studies. Fifty-three articles were included, of which 19 presented a questionnaire on BMW for healthcare workers. Nine proposed a validated questionnaire: four reported Cronbach's alpha, which ranged from 0.62 to 0.86. Results further emphasize the prevalence of Asian studies facing the problem of assessing KAP about BMW management using specific tools. Overall, 14 questionnaires were designed in Asia, two in Africa, one in America, one in Australia, and one questionnaire was elaborated in Europe, in Spain. This systematic review highlighted the need of creation of validated and methodologically high-quality questionnaires. Therefore, there is the need of new cross-sectional studies to investigate these problems, improving generalization, and facilitating international comparison of research findings